Workplace democracy in the lab - Philip Mellizo; Jeffrey P. Carpenter; Peter Hans Matthews (Institute for the Study of Labor (IZA), 2011)
While intuition suggests that empowering workers to have some say in the control of the firm is likely to have beneficial incentive effects, empirical evidence of such an effect is hard to come by because of numerous confounding factors in the naturally occurring data. We report evidence from a real-effort experiment confirming that worker performance is sensitive to the process used to select the compensation contract. Groups of workers that voted to determine their compensation scheme provided significantly more effort than groups that had no say in how they would be compensated. This effect is robust to controls for the compensation scheme implemented and worker characteristics (i.e., ability and gender).
urn:nbn:de:101:1-201104113333
Keywords: C92; J33; J54; 330; real-effort experiment; workplace democracy; decision control rights; Arbeitsleistung; Leistungsmotivation; Vergütungssystem; Mitbestimmung; Kooperative Führung